Functional thinking in Kolb learning style: A causal-comparative study - Sucipto, Lalu; Syawahid, Muhammad; Bahurudin Setambah, Mohd Afifi (Beta: Jurnal Tadris Matematika, 2024)
[English]: This study aims to elucidate variations in students’ functional thinking across divergent, convergent, assimilator, and accommodator learning styles. A causal-comparative study involving 137 student samples was conducted randomly from 214 students enrolled in grade 8 of junior high schools (MTsN 3) in Mataram, Lombok, Indonesia. Data collection for students’ functional thinking utilized three types of tasks, comprising two linear pattern tasks and one non-linear pattern task. Students’ learning style data were obtained from the Kolb learning style inventory (KLSI), comprising 12 statement items. Descriptive analysis revealed that the distribution of students’ Kolb learning styles was as follows: 29.93% divergent learning styles, 24.82% convergent learning styles, 17.52% assimilator learning styles, and 27.74% accommodator learning styles. On a scale of 0-100, the average functional thinking of students was 67.90, while the average functional thinking of students with divergent learning styles was 73, convergent 64.5, assimilator 69.9, and accommodator 64.2. The ANOVA test results yielded an F test value of 10.297 with a significant value of 0.0, indicating significant differences in students’ functional thinking among students with divergent, convergent, assimilator, and accommodator learning styles. Furthermore, the students with divergent learning styles exhibited the highest mean (m = 73) compared to the other groups. The research outcomes can serve as a basis for mathematics learning design based on students’ learning styles. [Bahasa]: Penelitian ini bertujuan untuk mengetahui perbedaan berpikir fungsional siswa dengan gaya belajar divergen, konvergen, asimilator dan akomodator. Penelitian causal-comparative ini melibatkan 137 sampel siswa yang diambil secara acak dari 214 siswa kelas 8 Madrasah Tsanawiyah Negeri (MTsN) 3 Mataram, Lombok, Indonesia. Data berpikir fungsional siswa dikumpulkan melalui tiga jenis tugas, yang terdiri dari dua tugas pola linier dan satu tugas pola non-linier. Data gaya belajar diperoleh dari Kolb learning style inventory (KLSI), yang terdiri dari dua belas item pernyataan. Analisis deskriptif mengungkapkan bahwa distribusi gaya belajar Kolb siswa adalah sebagai berikut: 29.93% gaya belajar divergen, 24.82% gaya belajar konvergen, 17.52% gaya belajar asimilator, dan 27.74% gaya belajar akomodator. Pada skala 0-100, rata-rata berpikir fungsional siswa adalah 67.90, sedangkan rata-rata berpikir fungsional siswa dengan gaya belajar divergen, konvergen, assimilator, dan akomodator secara berturut-turut adalah 73, 64.5, 69.9, dan 64.2. Hasil ANOVA menunjukkan nilai uji F sebesar 10.297 dengan signifikansi 0.0, artinya terdapat perbedaan yang signifikan kemampuan berpikir fungsional keempat kelompok siswa tersebut. Lebih jauh, kelompok siswa dengan gaya belajar divergen menunjukkan rerata tertinggi (m = 73) dibandingkan dengan ketiga kelompok lainnya. Hasil penelitian ini dapat dijadikan sebagai acuan dalam mendesain pembelajaran matematika berdasarkan gaya belajar siswa.